Adsorption-photocatalysis of organic dyes using empty fruit bunch activated carbon-metal oxide photocatalyst. (December 2018) - Loo, Wei Wen; Pang, Yean Ling; Wong, Kam Huei; Lim, Steven; Mah, Shee Keat
Abstract: This study reports on the adsorption-photocatalysis degradation of organic dyes by utilizing zinc oxide (ZnO) photocatalyst supported on empty fruit bunch (EFB) derived activated carbon (AC) under visible light irradiation. XRD diffraction patterns of AC/ZnO sample indicated the presence of AC and ZnO. SEM analysis illustrated that ZnO particles were spherical-shaped and agglomerated, AC exhibited porous structure while AC/ZnO had agglomerated particles along the porous structure. EDX results showed that AC/ZnO sample consists of C, O and Zn elements with minimal Si and K impurities. The optimum operating conditions for adsorption-photocatalytic degradation to achieve 100 % in 50 min were initial Congo red concentration of 10 mg/L, AC/ZnO catalyst loading of 1.25 g/L, solution pH of 3 and solution temperature of 55 °C. The determination of oxygen demand analysis (64.29 % removal) indicated that only partial Congo red was being degraded due to the generation of intermediate products which were more difficult to be oxidized compared to their parent organic dye compounds. Kinetic studies which were also carried out at different solution temperatures (35, 40, 45, 50 and 55 °C) suggested that the degradation process of Congo red followed pseudo-second order model with an estimated activation energy of 86.27 kJ/mol.